2020
DOI: 10.4081/or.2020.8656
|View full text |Cite
|
Sign up to set email alerts
|

Surgical implications of the hip-spine relationship in total hip arthroplasty

Abstract: Total hip arthroplasty (THA) is considered the most successful orthopedic surgical procedure of the last century with excellent survivorship up to 20-years. However, instability remains a major issue representing the most common reason for revision after THA. Hip-spine relationship has gained progressive interest between arthroplasty surgeons and its understanding is crucial in order to identify high-risk patients for postoperative dislocation. Spinal deformity and abnormal spinopelvic mobility have been assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…This means that their value changes with body position (31), which must be taken into account when planning total hip arthroplasty. Spinal deformity and abnormal pelvic mobility have been associated with an increased risk of instability, dislocation and revision (32), and as such, patients with suspected spino-pelvic mobility pathology should be identified prior to performing THA and have a comprehensive radiographic examination, which should include a weight-bearing AP pelvic view as well as sitting and standing lateral projections (33), which would not be possible using CT-based 3D templating.…”
Section: Discussionmentioning
confidence: 99%
“…This means that their value changes with body position (31), which must be taken into account when planning total hip arthroplasty. Spinal deformity and abnormal pelvic mobility have been associated with an increased risk of instability, dislocation and revision (32), and as such, patients with suspected spino-pelvic mobility pathology should be identified prior to performing THA and have a comprehensive radiographic examination, which should include a weight-bearing AP pelvic view as well as sitting and standing lateral projections (33), which would not be possible using CT-based 3D templating.…”
Section: Discussionmentioning
confidence: 99%
“…and Mancino et al. recommend that prior to THA, all patients must undergo standing, supine, and sitting lateral radiographs of the pelvis and the lumbar spine [ 47 , 48 ]. The views should ideally include L1 or, at the least, the level of L3, as most of the lumbar motion happens between L3 and L5 [ 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a lumbar stiffness will have to be compensated by more hip flexion when sitting and conversely, hip stiffness will require more lumbar flexion 8 . For this reason, many authors suggested to adjust the orientation of the hip implant according to spino‐pelvic mobility categories to compensate for possible stiffness and limit the risks of dislocation or impingement 4,9–14 . Yet, there is still today no consensus in the literature about the exact definition of these categories and their associated recommendations 15 …”
Section: Introductionmentioning
confidence: 99%